The use of electron linacs for detection of C-, N-, O- containing substances - Dovbnya, A.N.; Yegorov, A.M.; Bykov, V.T.; Khomykov, G.K.; Nemashkalo, B.A.; Pugachev, G.D.; Vodin, A.N.; Zaitsev, B.V.; Zhuk, V.V. (Вопросы атомной науки и техники, 2004)
The detection of concealed explosives (CE) has presently become the burning problem for the mankind. In particular, the problem is related to both clearing the open country of plastic mines and the detection of any CE, drugs,
etc. The creation of compact 60...100 MeV electron accelerators makes it possible to produce sharply directed
bremsstrahlung beams. For identification of ¹⁴N nuclei as main CE constituents, the following reactions are used
with production of ¹²B and ¹²N. Electrons were accelerated up to energies between 22 and 40 MeV at a pulse length
of 3.8 µs, a pulse-repetition frequency from 6.25 to 50 Hz, and a pulse current of ~20 mA. The bremsstrahlung gamma-rays were detected by a NaJ(TL) detector. Carbamide [(NH₂)₂CO] was used as a nitrogen target. For identification of ¹²N and ¹²B decay curves were measured. The signal/noise was 5. Results suggest the conclusion that the
present method of detecting CE and C-,N-,O- containing substances has encouraging prospects. Проблема виявлення прихованих вибухових речовин (ВР) придбала в даний час для людства надзвичайну актуальність. Це пов'язано з розмінуванням на відкритій місцевості безкорпусних мін і виявленням
ВР будь-якого типу в тому числі й інших речовин, що містять C-,N-,O-. Створення компактних прискорювачів електронів з енергією 60...100 МеВ дозволяє одержати вузькоспрямовані пучки гальмівних γ-квантів.
Для ідентифікації ядер ¹⁴N - основного компонента ВР використовуються реакції з утворенням ¹²В і ¹²N.
Електрони прискорювалися до енергій 22...40 МеВ, при тривалості імпульсу 3,8 мкс, частоті проходження
від 6,25 до 50 Гц і току в імпульсі ~20 мА. Гальмівне γ-випромінювання реєструвалося детектором Na(Tl).
Як азотна мішень використовувався карбамід [(NH₂)₂CO]. Для ідентифікації ¹²В і ¹²N були обмірювані криві
розпаду. Співвідношення сигнал/шум складало 5. Результати дозволяють зробити висновок, що даний засіб
виявлення ВР і інших речовин, що містять C-,N-,O-, має підбадьорюючі перспективи. Проблема обнаружения скрытых взрывчатых веществ (ВВ) приобрела в настоящее время для человечества чрезвычайную актуальность. Это связано с разминированием на открытой местности бескорпусных
мин и обнаружением ВВ любого типа, в том числе и других C-, N-, O- -содержащих веществ. Создание
компактных ускорителей электронов с энергией 60...100 МэВ позволяет получить узконаправленные пучки
тормозных γ-квантов. Для идентификации ядер ¹⁴N – основного компонента ВВ, используются реакции с образованием ¹²В и ¹²N. Электроны ускорялись до энергий 22...40 МэВ, при длительности импульса 3,8 мкс, частоте следования от 6,25 до 50 Гц и токе в импульсе ~20 мА. Тормозное γ–излучение регистрировалось детектором NaI(Tl).В качестве азотной мишени использовался карбамид [(NH₂)₂CO]. Для идентификации ¹²В и
¹²N были измерены кривые распада. Соотношение сигнал/шум составляло 5. Результаты позволяют сделать
вывод, что данный способ обнаружения ВВ и других C-,N-,O- -содержащих веществ имеет обнадеживающие перспективы.